2013
DOI: 10.15580/gjas.2013.3.100713891
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change: Matching Growing Season Length with Maize Crop Varietal Life Cycles in Semi-Arid Regions of Zimbabwe

Abstract: Climate change is set to increase the risk and uncertainty of maize production in the semi-arid Regions of Zimbabwe. The study had the objective to determine the existence of climate change in Masvingo District using the long term behaviour of the growing season length and its parameters over a period of 31 years , and to match the life cycle period of locally available maize, sorghum and pearl millet varieties with growing season length. The onset of the rain season was found to be an important indicator of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
2
3
0
Order By: Relevance
“…This was due to the early start and later end of the growing season. This is in agreement with Mubvuma (2013) who showed that there was a strong correlation between the onset of the rainy season and the LGS. He showed that the LGS increases with the earlier onset of the rainy season.…”
Section: Resultssupporting
confidence: 93%
“…This was due to the early start and later end of the growing season. This is in agreement with Mubvuma (2013) who showed that there was a strong correlation between the onset of the rainy season and the LGS. He showed that the LGS increases with the earlier onset of the rainy season.…”
Section: Resultssupporting
confidence: 93%
“…Furthermore, farming seasons run short and rainfall is no longer effective, and its period of onset is late November to early December. The results also con rm the ndings of Mubvuma [40] that short farming seasons are characterized by droughts in the start and middle of the seasons, making rain-fed agriculture to be di cult. In addition, this concurs with Chikodzi et al [44], who observed that the catchment is no longer viable for livestock production due to the increase in aridity.…”
Section: Resultssupporting
confidence: 81%
“…Table 1 shows that the regions with longer WRS experienced more rainy days (i.e., correlation coefficient 0.9627) and also received a significant share of AP in the RS. Many experts in the field (e.g., Kanemasu et al, 1990; Mubvuma, 2013; Mugalavai et al, 2008; Sivakumar, 1988) also believed that in general, earlier ORS leads to a longer RS.…”
Section: Resultsmentioning
confidence: 99%